PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT DAN ORGANIZATIONAL CULTURE TERHADAP WORK-LIFE BALANCE KARYAWAN - Syafitri Andra, Resti; Nayati Utami, Hamidah; Wulida Afrianty, Tri (FIA UB, 2022)
This study aims to determine the effect of perceived organizational support and organizational culture on work-life balance of millennial employees at PT Incasi Raya Inderapura. Strong corporate competition forces employees to be able to do many things well in order to achieve organizational objectives. Organizations often forget that employees are confronted not only with the requirements of the company, but also with those of their personal lives. The high demands of work and personal life can damage employee focus and performance. Organizations must therefore provide support to employees and facilitate work-life balance. Maintaining a balanced professional and personal life is important to employees. To ensure the proper implementation of WLB policies, a supportive organizational culture is needed. In this study, a quantitative and descriptive methodology was employed. It was conducted in the manufacturing industry, PT. Incasi Raya Indrapura. Eighty Millennial employees were selected according to the census method. The data were collected by questionnaires and observations. It was then analysed using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results of the study indicated that the perceived organization has a significant positive impact on work-life balance.